0922 Nightly Associations Between Pre-Bedtime Activity, Actigraphic Light, and Sleep in Children With ASD and Insomnia. (27th May 2020) - McGovney, K D; Curtis, A F; Mazurek, M; Chan, W S; Deroche, C B; Munoz, M; Davenport, M; Takamatsu, S; Takahashi, N; Muckerman, J; McCann, D; Sahota, P; et al.
Abstract: Introduction: Approximately two thirds of children with Autism Spectrum Disorder (ASD) suffer from chronic insomnia. Current behavioral interventions for insomnia in children with ASD use sleep hygiene guidelines to educate parents and their children regarding sleep promoting habits. However, the relationship between pre-bedtime physical activity/light and sleep is understudied in ASD. The current study examined daily associations between pre-bedtime actigraphically assessed activity/light levels and objective/subjective sleep outcomes in children with ASD and insomnia. Methods: Thirty children (Mage=8.5 yrs, SD=1.78 yrs) with comorbid ASD and insomnia completed 14 days of actigraphy measuring ambient white light intensity and activity levels every 30 seconds. Validated sleep scoring algorithms (in Actiware V. 6.0.9) estimated objective sleep onset latency (SOL), total sleep time (TST), wake time after sleep onset (WASO), and average activity/light levels 30, 60, and 120 mins prior to bedtime. Additionally, average activity/light levels 120-240, and 240-360 mins prior to bedtime were computed. Children also completed 14 daily sleep diaries (with parental assistance) measuring subjective reports of the same sleep parameters. Associations between daily estimations of pre-bedtime activity levels, light, and nighttime objective and subjective sleep were examined through multilevel modelling. Bonferroni corrections were performed to account for multiple comparisons. Results: After Bonferroni corrections (p<.025 significance level), greater activity within 30 minutes (B=0.0465, p=.0093) and 60 minutes (B=0.0681, p=.0005) of bedtime were associated with longer subjective SOL. Pre-bedtime light exposure was not a significant predictor of sleep outcomes. Conclusion: Results suggest that in general, variations in daily pre-bedtime activity, but not light, are associated with worse nightly subjective SOL in children with ASD and insomnia. Findings support that sleep hygiene recommendations in children with ASD include avoidance of higher levels of pre-sleep physical activity. Prospective studies examining temporal causal relationships between pre-bedtime activity and sleep in ASD are warranted. Support: Research was supported by a University of Missouri Research Board award (McCrae, PI; Mazurek, Co-PI). Data collected as part of clinical trial NCT02755051 Targeting Sleep in Kids with Autism Spectrum Disorder at the University of Missouri (PI: McCrae).